Bluestar's acquisition of Adisseo. A - McFarlan, F. Warren (SAGE knowledge. Cases., 2016)
In early January 2006, Ren Jianxin, general manager of ChemChina sat in his office as the soft, warm winter sunshine passed through the window glass. A few days earlier, Bluestar had completed its acquisition of Adisseo in Brussels, Belgium. He was pleased that he had led Bluestar's management team in what had initially seemed impossible. A knock on the door interrupted his thoughts. It was his Administrative Assistant, informing him that the executive team was meeting to discuss matters post acquisition of Adisseo.